Perbedaan Hasil Belajar Kognitif Siswa Pada Pembelajaran Daring Melalui Google Classroom dan Whatsapp Mesenger Di SMP Negeri 4 Bengkulu Tengah: (Differences in Student Cognitive Learning Outcomes in Online Learning Through Google Classroom and Whatsapp Messenger at SMP Negeri 4 Bengkulu Tengah) - Alianto Alianto; R Hasan; Irwandi Irwandi (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2021)
Cognitive learning outcomes of students in learning biology are still low. This study aims to determine the differences in students' cognitive learning outcomes in online learning through google classroom and whatsapp messenger at SMP Negeri 4 Bengkulu Tengah. The research was carried out in January-March 2021, using pre-experimental research methods, pre-experimental one group pre-test-post-test design. The population is class VIII SMPN 4 Bengkulu Tengah, totaling 86 students, with a sample of 43 students. Collecting data with test questions of students' cognitive learning outcomes. The results showed that there was no difference between students' cognitive learning outcomes in online learning through google classroom and whatsapp messenger at SMPN 4 Bengkulu Tengah. Abstrak. Hasil belajar kognitif siswa dalam pembelajaran biologi masih rendah. Penelitian ini bertujuan untuk mengetahui perbedaan hasil belajar kognitif siswa pada pemebelajaran daring melalui google classroom dan whatsapp mesenger Di SMP Negeri 4 Bengkulu Tengah. Penelitian dilaksanakan pada bulan Januari-Maret 2021, menggunakan metode penelitian pra eksperimen, desain pre-eksperiment one group pre-test-post-test. Populasi adalah siswa kelas VIII SMPN 4 Bengkulu Tengah yang berjumlah 86 siswa, dengan sampel 43 siswa. Pengumpulan data dengan soal tes hasil belajar kognitif siswa. Hasil penelitian menunjukkan bahwa tidak terdapat perbedaan antara hasil belajar kognitif siswa pada pembelajaran daring melaui google classroom dan whatsapp mesenger Di SMPN 4 Bengkulu Tengah.